7
$\begingroup$

How to prove without using Euler sums that

$$I=\int_0^1\frac{\ln x\ln(1+x)}{1-x}\ dx=\zeta(3)-\frac32\ln2\zeta(2)$$

where $\zeta$ is the Riemann zeta function.

We can relate this integral to some Euler sum as follows:

\begin{align} I&=-\sum_{n=1}^\infty\frac{(-1)^n}{n}\int_0^1\frac{x^n\ln x}{1-x}\ dx\\ &=-\sum_{n=1}^\infty\frac{(-1)^n}{n}(H_n^{(2)}-\zeta(2))\\ &=-\sum_{n=1}^\infty\frac{(-1)^nH_n^{(2)}}{n}-\ln2\zeta(2) \end{align}

Also the integral $I$ can be related to $\sum_{n=1}^\infty\frac{(-1)^nH_n}{n^2}$. So I am looking for a different way to evaluate $I$ besides using these two sums.

$\endgroup$
6
$\begingroup$

\begin{align}J&=\int_0^1 \frac{\ln x\ln(1+x)}{1-x}\,dx\end{align} Always the same story...

For $x\in [0;1]$ define the function $R$ by,\begin{align}R(x)&=\int_0^x \frac{\ln t}{1-t}\,dt\\ &=\int_0^1 \frac{x\ln(tx)}{1-tx}\,dt\\ J&=\Big[R(x)\ln(1+x)\Big]_0^1-\int_0^1 \frac{R(x)}{(1+x)} dx\\ &=-\zeta(2)\ln 2-\int_0^1 \int_0^1 \frac{x\ln(tx)}{(1-tx)(1+x)}\,dt\,dx\\ &=-\zeta(2)\ln 2-\int_0^1 \left(\int_0^1 \frac{x\ln t}{(1-tx)(1+x)}\,dx\right)\,dt-\int_0^1 \left(\int_0^1 \frac{x\ln x}{(1-tx)(1+x)}\,dt\right)\,dx\\ &=-\zeta(2)\ln 2+\int_0^1\left[\frac{\ln(1-tx)}{t(1+t)}+\frac{\ln(1+x)}{1+t}\right]_{x=0}^{x=1}\ln t\,dt+\int_0^1\left[\frac{\ln(1-tx)}{1+x}\right]_{t=0}^{t=1}\ln x\,dx\\ &=-\zeta(2)\ln 2+\int_0^1 \frac{\ln(1-t)\ln t}{t(1+t)}\,dt+\ln 2\int_0^1 \frac{\ln t}{1+t}\,dt+\int_0^1 \frac{\ln(1-x)\ln x}{1+x}\,dx\\ &=-\zeta(2)\ln 2+\int_0^1 \frac{\ln(1-t)\ln t}{t}\,dt+\ln 2\int_0^1 \frac{\ln t}{1+t}\,dt\\ &=-\zeta(2)\ln 2+\frac{1}{2}\left(\Big[\ln^2 x\ln(1-x)\Big]+\int_0^1 \frac{\ln^2 t }{1-t}\,dt\right)+\ln 2\left(\int_0^1 \frac{\ln t}{1-t}\,dt-\int_0^1 \frac{2t\ln t}{1-t^2}\,dt\right) \end{align} In the last integral perform the change of variable $y=t^2$, \begin{align}J&=-\zeta(2)\ln 2+\frac{1}{2}\int_0^1 \frac{\ln^2 t}{1-t}\,dt+\ln 2\left(\int_0^1 \frac{\ln t}{1-t}\,dt-\frac{1}{2}\int_0^1 \frac{\ln t}{1-t}\,dt\right)\\ &=-\frac{3}{2}\zeta(2)\ln 2+\frac{1}{2}\times 2\zeta(3)\\ &=\boxed{-\frac{3}{2}\zeta(2)\ln 2+\zeta(3)} \end{align} NB: i assume,\begin{align}R(1)&=\int_0^1 \frac{\ln t}{1-t}\,dt\\ &=-\zeta(2)\\ \int_0^1 \frac{\ln^2 t}{1-t}\,dt&=2\zeta(3)\end{align}

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ nice approach.. $\endgroup$ – Ali Shadhar Sep 15 '19 at 23:43
6
$\begingroup$

Start off with the substitution $x\to \frac{1-x}{1+x}$ to get: $$\require{cancel} I=\int_0^1 \frac{\ln x\ln(1+x)}{1-x}dx=\int_0^1 \frac{\ln\left(\frac{1-x}{1+x}\right)\ln\left(\frac{2}{1+x}\right)}{x}dx-\int_0^1 \frac{\ln\left(\frac{1-x}{1+x}\right)\ln\left(\frac{2}{1+x}\right)}{1+x}dx$$

$$X=\int_0^1 \frac{\ln(1-x)\ln 2 -\ln(1-x)\ln(1+x)-\ln(1+x)\ln 2+\ln^2(1+x)}{x}dx$$ $$Y=\int_0^1 \frac{\ln(1-x)\ln 2 -\ln(1-x)\ln(1+x)-\ln(1+x)\ln 2+\ln^2(1+x)}{1+x}dx$$


$$I_1=\ln 2\int_0^1 \frac{\ln(1-x)}{x}dx=\color{blue}{-\ln 2 \zeta(2)}$$ $$I_2=-\int_0^1 \frac{\ln(1-x)\ln(1+x)}{x}dx=\color{red}{\frac{5}{8}\zeta(3)}$$ $$I_3=-\ln 2 \int_0^1 \frac{\ln(1+x)}{x}dx=\color{blue}{-\frac{\ln 2}{2}\zeta(2)}$$ $$I_4=\int_0^1 \frac{\ln^2(1+x)}{x}dx=\color{red}{\frac{\zeta(3)}{4}}$$ $$I_5=\ln 2\int_0^1 \frac{\ln(1-x)}{1+x}dx=\cancel{\frac{\ln^3 2}{2}}-\cancel{\ln 2\frac{\zeta(2)}{2}}$$ $$I_6=-\int_0^1 \frac{\ln(1-x)\ln(1+x)}{1+x}dx =\cancel{-\frac{\ln^3 2}{3}}+\cancel{\ln 2\frac{\zeta(2)}{2}}-\color{red}{\frac{\zeta(3)}{8}}$$ $$I_7=-\ln 2 \int_0^1 \frac{\ln(1+x)}{1+x}dx=\cancel{-\frac{\ln^3 2}{2}}$$ $$I_8=\int_0^1 \frac{\ln^2(1+x)}{1+x}dx=\cancel{\frac{\ln^3 2}{3}}$$


$$I=X-Y=(I_1+I_2+I_3+I_4)-(I_5+I_6+I_7+I_8)=\boxed{\zeta(3)-\frac32 \ln 2 \zeta(2)}$$

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ (+1) For the brilliance of the solution. $\endgroup$ – user97357329 Sep 8 '19 at 17:08
  • 1
    $\begingroup$ nice idea Zacky. $\endgroup$ – Ali Shadhar Sep 8 '19 at 17:08
  • $\begingroup$ @Zacky would you mind writing the website you sent me before where i can find $\int_0^1\frac{\ln^3(1+x)\ln(1-x)}{x}\ dx$? because I posted solution there and I need it as a ref. $\endgroup$ – Ali Shadhar Sep 8 '19 at 19:19
  • $\begingroup$ @AliShather artofproblemsolving.com/community/u380742h1883703p12826640 $\endgroup$ – Zacky Sep 8 '19 at 20:43
  • 1
    $\begingroup$ @Zacky thank you so much $\endgroup$ – Ali Shadhar Sep 8 '19 at 20:48
3
$\begingroup$

You might need the first generalization from the preprint A simple strategy of calculating two alternating harmonic series generalizations by Cornel Ioan Valean. All the calculations are accomplished by avoiding the evaluation of Euler sums.

$$ \sum_{n=1}^{\infty} (-1)^{n-1}\frac{H_n^{(m)}}{n}=\frac{(-1)^m}{(m-1)!}\int_0^1\frac{\displaystyle \log^{m-1}(x)\log\left(\frac{1+x}{2}\right)}{1-x}\textrm{d}x $$ $$=\frac{1}{2}\biggr(m\zeta (m+1)-2\log (2) \left(1-2^{1-m}\right) \zeta (m)$$ $$-\sum_{k=1}^{m-2} \left(1-2^{-k}\right)\left(1-2^{1+k-m}\right)\zeta (k+1)\zeta (m-k)\biggr).$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ I am familiar with these generalizations .. very useful but how about to do it on our own? $\endgroup$ – Ali Shadhar Sep 8 '19 at 15:59
  • $\begingroup$ I started from the assumption you weren't aware of it since you didn't mention it, and then you didn't ask for ways which didn't appear in the mathematical literature yet. $\endgroup$ – user97357329 Sep 8 '19 at 16:03
  • $\begingroup$ I am very familiar with Cornel's papers but I am really into independent solutions ( if possible) that does not reply much on other results/ generalizations. $\endgroup$ – Ali Shadhar Sep 8 '19 at 16:22
  • $\begingroup$ Of course you are into independent solutions. The manipulations with double integrals seems to make it very easy. $\endgroup$ – user97357329 Sep 8 '19 at 16:51
  • $\begingroup$ that's the way to go :) $\endgroup$ – Ali Shadhar Sep 8 '19 at 16:55
3
$\begingroup$

Consider the integral $$K=\int_0^1\frac{\operatorname{Li}_2(x)}{1+x}\ dx$$

By applying IBP we have

$$K=\ln(2)\zeta(2)+\int_0^1\frac{\ln(1-x)\ln(1+x)}{x}\ dx\tag{1}$$

.


On the other hand

\begin{align} K&=\int_0^1\frac{\operatorname{Li}_2(x)}{1+x}\ dx=\int_0^1\frac{1}{1+x}\left(\int_0^1-\frac{x\ln u}{1-xu}\ du\right)\ dx\\ &=\int_0^1\ln u\left(\int_0^1\frac{-x}{(1+x)(1-ux)}\ dx\right)\ du\\ &=\int_0^1\ln u\left(\frac{\ln2}{1+u}+\frac{\ln(1-u)}{u}-\frac{\ln(1-u)}{1+u}\right)\ du\\ &=\ln2\int_0^1\frac{\ln u}{1+u}\ du+\int_0^1\frac{\ln u\ln(1-u)}{u}\ du-\color{blue}{\int_0^1\frac{\ln u\ln(1-u)}{1+u}\ du}\\ &\overset{\color{blue}{IBP}}{=}\ln2\left(-\frac12\zeta(2)\right)+\zeta(3)\color{blue}{-\int_0^1\frac{\ln u\ln(1+u)}{1-u}du+\int_0^1\frac{\ln(1-u)\ln(1+u)}{u}du}\tag{2} \end{align}


Combining (1) and (2) we get

$$\int_0^1\frac{\ln x\ln(1+x)}{1-x}\ dx=\zeta(3)-\frac32\ln2\zeta(2)$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ (+1) Definitely one of the best solutions. $\endgroup$ – user97357329 Sep 8 '19 at 17:02
  • $\begingroup$ Thank you @user97357329 . $\endgroup$ – Ali Shadhar Sep 8 '19 at 17:21
  • $\begingroup$ I think one can make things a little more simpler because $(a+b)^2-(a-b)^2=4ab$ $\endgroup$ – FDP Sep 9 '19 at 17:12
  • $\begingroup$ @FDP this method is done by Zacky here math.stackexchange.com/q/3085715 but thats not enough to solve the problem. $\endgroup$ – Ali Shadhar Sep 9 '19 at 17:43
  • $\begingroup$ @Ali Shather: if you want to compute $\displaystyle \int_0^1\frac{\ln(1-x)\ln(1+x)}{x}\ dx$, for me, it's enough. $\endgroup$ – FDP Sep 9 '19 at 18:54
0
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ $\ds{\bbox[5px,#ffd]{\int_{0}^{1}{\ln\pars{x}\ln\pars{1 + x} \over 1-x}\,\dd x = \zeta\pars{3} - {3 \over 2}\,\ln\pars{2}\zeta\pars{2}}:\ \approx 0.5082\ {\Large ?}}$.


\begin{align} &\bbox[5px,#ffd]{\int_{0}^{1}{\ln\pars{x}\ln\pars{1 + x} \over 1 - x}\,\dd x} = {1 \over 2}\int_{0}^{1}{2\ln\pars{x}\ln\pars{1 + x} \over 1 - x}\,\dd x \\[5mm] = &\ {1 \over 2}\int_{0}^{1}{\ln^{2}\pars{x} + \ln^{2}\pars{1 + x} - \bracks{\ln\pars{x} - \ln\pars{1 + x}}^{\, 2} \over 1 - x}\,\dd x \\[5mm] = &\ {1 \over 2}\int_{0}^{1}{\ln^{2}\pars{x} \over 1 - x}\,\dd x + {1 \over 2}\int_{0}^{1}{\ln^{2}\pars{1 + x} - \ln^{2}\pars{2} \over 1 - x}\,\dd x \\[2mm] & \!\!\!\! -{1 \over 2}\int_{0}^{1} \bracks{\ln^{2}\pars{x \over x + 1} - \ln^{2}\pars{2}} \,{\dd x \over 1 - x} \end{align} In the $\underline{second}$ integral I'll make the change $\ds{1 + x \mapsto 2x}$ while $\ds{x/\pars{x + 1} \mapsto x}$ in the $\underline{third}$ one. Then, \begin{align} &\bbox[5px,#ffd]{\int_{0}^{1}{\ln\pars{x}\ln\pars{1 + x} \over 1 - x}\,\dd x} \\[5mm] = &\ {1 \over 2}\int_{0}^{1}{\ln^{2}\pars{x} \over 1 - x}\,\dd x + {1 \over 2}\int_{1/2}^{1}{\ln^{2}\pars{2x} - \ln^{2}\pars{2} \over 1 - x}\,\dd x \\[2mm] & \!\!\!\! -{1 \over 2}\bracks{% -\int_{0}^{1/2}{\ln^{2}\pars{x} - \ln^{2}\pars{2} \over 1 - x} \,\dd x + 2\int_{0}^{1/2}{\ln^{2}\pars{x} - \ln^{2}\pars{2} \over 1 - 2x} \,\dd x} \\[5mm] = &\ {1 \over 2}\int_{0}^{1}{\ln^{2}\pars{x} \over 1 - x}\,\dd x + {1 \over 2}\int_{1/2}^{1}{\ln^{2}\pars{2x} - \ln^{2}\pars{2} \over 1 - x}\,\dd x \\[2mm] & \!\!\!\! + \bracks{% {1 \over 2}\int_{0}^{1/2}{\ln^{2}\pars{x} \over 1 - x}\,\dd x - {1 \over 2}\ln^{3}\pars{2} - {1 \over 2}\int_{0}^{1}{\ln^{2}\pars{x/2} - \ln^{2}\pars{2} \over 1 - x}\,\dd x} \\[5mm] & \stackrel{\mrm{IBP}}{=}\,\,\, -\int_{0}^{1}\mrm{Li}_{2}'\pars{x}\ln\pars{x}\,\dd x + \bracks{% {1 \over 2}\ln^{3}\pars{2} -\int_{1/2}^{1}\mrm{Li}_{2}'\pars{x}\ln\pars{2x}\,\dd x} \\[2mm] & \phantom{\stackrel{\mrm{IBP}}{=}\,\,\,\,\,} + \bracks{{1 \over 2}\ln^{3}\pars{2} -\int_{0}^{1/2}\mrm{Li}_{2}'\pars{x}\ln\pars{x}\,\dd x} \\[2mm]& \phantom{\stackrel{\mrm{IBP}}{=}\,\,\,\,\,} -{1 \over 2}\ln^{3}\pars{2} + \int_{0}^{1}\mrm{Li}_{2}'\pars{x}\ln\pars{x \over 2}\,\dd x \\[5mm] & \stackrel{\mrm{IBP}}{=}\,\,\, \int_{0}^{1}\mrm{Li}_{3}'\pars{x}\,\dd x + {1 \over 2}\ln^{3}\pars{2} -\mrm{Li}_{2}\pars{1}\ln\pars{2} + \int_{1/2}^{1}\mrm{Li}_{3}'\pars{x}\,\dd x \\[2mm] & \phantom{\stackrel{\mrm{IBP}}{=}\,\,\,\,\,} -\mrm{Li}_{2}\pars{1 \over 2}\ln\pars{1 \over 2} + \int_{0}^{1/2}\mrm{Li}_{3}'\pars{x}\,\dd x +\mrm{Li}_{2}\pars{1}\ln\pars{1 \over 2} \\[2mm] & \phantom{\stackrel{\mrm{IBP}}{=}\,\,\,\,\,} -\int_{0}^{1}\mrm{Li}_{3}'\pars{x}\,\dd x \\[5mm] & \stackrel{\mrm{IBP}}{=}\,\,\, \zeta\pars{3} + {1 \over 2}\ln^{3}\pars{2} -2\mrm{Li}_{2}\pars{1}\ln\pars{2} + \zeta\pars{3} - \mrm{Li}_{3}\pars{1 \over 2} \\[2mm] & \phantom{\stackrel{\mrm{IBP}}{=}\,\,\,\,\,} + \mrm{Li}_{2}\pars{1 \over 2}\ln\pars{2} + \mrm{Li}_{3}\pars{1 \over 2} - \zeta\pars{3} \\[5mm] & \stackrel{\mrm{IBP}}{=}\,\,\, {1 \over 2}\ln^{3}\pars{2} -2\,\mrm{Li}_{2}\pars{1}\ln\pars{2} + \zeta\pars{3} + \mrm{Li}_{2}\pars{1 \over 2}\ln\pars{2} \label{1}\tag{1} \\[5mm] & \phantom{\stackrel{\mrm{IBP}}{=}\,\,\,\,\,} = \bbx{\large\zeta\pars{3} - {3 \over 2}\,\ln\pars{2}\zeta\pars{2}} \approx 0.5082\label{2}\tag{2} \end{align}

In (\ref{1}) and (\ref{2}) I used $\ds{\mrm{Li}_{2}\pars{1} = \zeta\pars{2} = \pi^{2}/6}$ and the known values of $\ds{\mrm{Li}_{2}\pars{1/2}}$ and $\ds{\mrm{Li}_{3}\pars{1/2}}$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.